Diabetes mellitus masking an ectopic Cushing syndrome in a young male: a case report - Mohanty, Soumya R.; Manisha, Mallavarapu (International Journal of Research in Medical Sciences, 2025)
Ectopic adrenocorticotropic hormone (ACTH) secretion is a rare but important cause of Cushing syndrome, often associated with neuroendocrine tumors such as bronchial or gastrointestinal carcinoids. Its presentation can be subtle or atypical, delaying diagnosis and increasing morbidity. Herein this case report presents a 24-year-old male presenting with uncontrolled diabetes mellitus, polyuria, and weight loss (13 kg over 6 months). He exhibited proximal muscle weakness, broad purple striae, and extensive hyperpigmentation. Laboratory evaluation revealed markedly elevated 8 am serum cortisol 82 mcg/dl, midnight awake cortisol 211 mcg/dl, overnight dexamethasone suppression test (27.32 mcg/dl), plasma ACTH 320 pg/ml, and a non-suppressed (<50%) high-dose dexamethasone suppression test (16 mcg/dl). High-resolution computed tomography (HRCT) chest demonstrated multiple pulmonary nodules. Ga-68 DOTANOC PET-CT imaging revealed somatostatin receptor expression in bilateral lung nodules. Endobronchial biopsy confirmed atypical carcinoid tumor, Ki-67 index 4%. This case highlights the diagnostic complexity of ectopic ACTH syndrome, particularly in young adults presenting with rapidly worsening diabetes. The presence of significant pigmentation, proximal myopathy, and metabolic derangements were key clinical clues. Atypical carcinoid tumors exhibit intermediate biological behavior and require a multidisciplinary management approach including surgical resection, somatostatin analog therapy, and cortisol-lowering strategies. Ectopic ACTH syndrome should be considered in young patients with severe metabolic abnormalities, rapid weight loss, and hyperpigmentation. Early recognition and appropriate work-up can prevent complications and improve outcomes.